Article Human Capital an Islamic Perspective - Ifa Faizah Rohmah; Eti Jumiati (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
Human capital can also be referred to as the potential that everyone has to turn into a superior human being. The discussion of human capital is dissected through the eyes of Islam, namely the Qur'an. The goal is to find out what potential humans have to be developed. This discussion is analyzed through a library method that is sourced from the Qur'an, the theory of the human element from the perspective of Imam Al-Ghozali and several other supporting data. That is by dissecting the potentials of humans through the verses of the Qur'an. Imam Al-Ghozali classifies the human element in empathy, namely: heart, spirit, lust, and reason. These four things must support and balance each other so that personal human capital can be realized which has eight potentials in the Qur'an, namely: humans are perfect creatures, humans are spiritual beings, humans are social creatures, humans are caliphs on earth, humans are human beings. are creatures who are given the ability to try, whether male or female, humans are creatures who want justice and respect according to their competence, humans are creatures who like to consult, and humans are creatures that can change.